1977
DOI: 10.1254/jjp.27.153
|View full text |Cite
|
Sign up to set email alerts
|

Antidiuresis of Centrally Administered Amines and Peptides and Release of Antidiuretic Hormone from Isolated Rat Neurohypophysis

Abstract: Abstract-Effectsof biogenic amines and peptides on urine outflow and ADH release were studied using intracerebroventricular (i.c.v.) perfusion experiments and isolated neurohypophysis incubation studies. Decrease in the urine outflow was observed after norepinephrine, histamine and angiotensin II had been administered i.c.v.. The effect of norepinephrine was prevented by phentolamine.Phentolamine alone also acted as an antidiuretic.a-Adrenergic and histaminergic mechanisms may thus involved in ADH releasing sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Both antidiuretic and ADH releasing effects of noradrenaline were inhibited by phentolamine (15,20,21). This may be an a-adrenergic effect, as speculated by others (21).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Both antidiuretic and ADH releasing effects of noradrenaline were inhibited by phentolamine (15,20,21). This may be an a-adrenergic effect, as speculated by others (21).…”
Section: Discussionsupporting
confidence: 56%
“…Noradrenaline, when injected centrally, was an antidiuretic (15,19,20) and caused an increase in plasma ADH concentration (20,21). Both antidiuretic and ADH releasing effects of noradrenaline were inhibited by phentolamine (15,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Hisada et al (1977) found that antidiuresis in response to i.c.v. injected noradrenaline was inhibited by phentolamine but not propranolol.…”
Section: Discussionmentioning
confidence: 99%
“…Bridges et al, (1976) found that, in addition to its effect in vivo, dopamine in extremely low (femtogram) concentration provoked the release of vasopressin and oxytocin from the rat hypothalamus in vitro and, in much higher (nanogram) concentration, from the isolated neural lobe. Conversely, Johnston et al, (1975) found that dopamine inhibited the electrically-stimulated release of lysine vasopressin from the pig neural lobe in vitro whereas Yeo, Lockett and Heller (1972) and Hisada et al (1977) found that microgram quantities of dopamine did not alter hormone release from the rat neural lobe. Ruoff, Gosbee and Lederis (1974) applied nanogram doses of dopamine directly to the neural lobe of the anaesthetized rat by microinfusion via the transauricular route but could find no change in urine flow or conductivity.…”
Section: Tablementioning
confidence: 98%